The Influence of B2B Social Media Marketing and Relationship Marketing on Customer Relationship Management Effectiveness, WOM and Loyalty: A Mediator Analysis - Dao, Tuan Cong; Liao, Ying-Kai; Chen, Grace; Luu, Thi-Minh-Ngoc; Le, Thi Mai (International Review of Management and Marketing, 2024)
This research aims to investigate the relationships between Business to Business (B2B) social media marketing, customer relationship management effectiveness (CRME), word-of-mouth (WOM), and loyalty, while also examining the mediating role of relationship marketing. A total of 256 respondents were recruited from a machinery manufacturing company’s customer base, encompassing regions as Taiwan and other Asia countries to assess their perspectives on B2B marketing. The following results were derived: (1) B2B social media marketing significantly impacts customer relationship, further enhancing the firm’s performance; (2) Customer relationship management effectiveness and customer loyalty notably influence word-of-mouth (WOM); (3) Social media marketing influences on CRME, WOM, and customer loyalty can be mediated through relationship marketing. This study’s findings provide crucial references for future academic validations. Moreover, professionals aiming to craft effective B2B customer relationship strategies can leverage these results for considerable potential.